(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
When we look back at the 1920s and 1930s of the 20th century, we realize that, like all social life processes, the cultural and spiritual sphere also underwent a period of complexity and difficulty. The Soviet government and its ruling party, in their pursuit of establishing a socialist system across the entire country, understood the unique role of culture and the fact that many things could not be achieved without it. Therefore, from the early years of Soviet rule, they began to develop the process of cultural construction based on their own resources and ideologies.